Pan-Enteric Capsule Endoscopy: Current Applications and Future Perspectives - Rosa,Bruno (2024)
Abstract Background: The role of capsule endoscopy in the evaluation of the small bowel is well established, and current guidelines position it as a ﬁrst-line test in a variety of clinical scenarios. The advent of double-headed capsules further enabled the endoscopic assessment of colonic mucosa and the opportunity for a one-step noninvasive examination of the entire bowel (panenteric capsule endoscopy [PCE]). Summary: We reviewed the technical procedure and preparation of patients for PCE, as well as its current clinical applications and future perspectives. In non-stricturing and non-penetrating Crohn’sdisease affecting the small bowel and colon, PCE monitors disease activity by assessing mucosal healing, a major treatment outcome, with a higher diagnostic yield than cross-sectional imaging or conventional colonoscopy. Also in ulcerative colitis, double-headed capsules have been used to monitor disease activity noninvasively. Currently, validated scoring systems have been speciﬁcally devised for these double-headed capsules and permit a standardized assessment of the inﬂammatory burden. In suspected mid-lower digestive bleeding, some exploratory studies have demonstrated the feasibility and high diagnostic yield of PCE, which may work as a ﬁlter indicating which patients may beneﬁt of further invasive procedures, namely, for planned hemostatic procedures. The possibility of using PCE is also discussed in the context of polyposis syn-dromes with simultaneous involvement of the small intestine and colon. Key Messages: PCE is a feasible, effective, and safe diagnostic procedure to evaluate the small bowel and colon. It has been increasingly explored in the setting of inﬂammatory bowel diseases and, more recently, in suspected mid-lower digestive bleeding. PCE is expected to reduce the demand for invasive procedures and expand the scope of noninvasive intestinal evaluation in the coming future.